Advances of Non-coding RNA in Oral Cancer - FU Yuting; YANG Wenjun; JIANG Binyuan (Zhongliu Fangzhi Yanjiu, 2022)
Oral cancer is a common head and neck malignant tumor. Its molecular mechanism of pathogenesis is complex and needs further exploration. Non-coding RNAs account for more than 95% of human transcripts and include microRNAs, lncRNAs, and circRNAs. They are an important entry point for research on molecular mechanism of oral cancer. Non-coding RNAs and protein-coding genes constitute a complex regulatory system involved in the regulation of physiological and pathological processes. This review summarizes articles about oral cancer-related non-coding RNAs and presents valuable information from the perspectives of microRNA, lncRNA, and circRNA.